ChemInform Abstract: Palladium‐Catalyzed Aryl C—H Olefination with Unactivated, Aliphatic Alkenes. Issue 14 (April 2015) - Deb, Arghya; Bag, Sukdev; Kancherla, Rajesh; Maiti, Debabrata
Abstract: This Pd‐catalyzed, chelation‐assisted C‐H olefination between unactivated, aliphatic olefins and phenylacetic acid substrates reveals a broad substrate scope, which is enabled by a bidendate directing group together with the use of the racemic binaphthyl ligand to enhance the catalytic activity of the Pd(II) species.